The relation between high-performance work systems and product innovativeness: The mediating role of technological capabilities and the moderating role of university-industry collaboration - Alpkan, Lütfihak; Gemici, Evrim (Elsevier BV, 2023)
The aim of this paper is to investigate the relationship between high-performance work systems (HPWS) and product innovativeness. Drawing on the dynamic capabilities perspective, this study examines the mediating role of technological capabilities in this relationship as well as considering the moderating role of university and industry (U-I) collaboration between HPWS and technological capabilities. Data for this study were collected from 228 firms in the Turkish automobile industry. Research hypotheses were examined by the partial least squares structural equation modelling technique using SmartPLS. Results revealed that technological capabilities mediated the relationship between HPWS and product innovativeness, and U-I collaboration had a moderating effect in the relationship between HPWS and technological capabilities. While this study examines the role of technological capabilities in the relationship between HPWS and product innovativeness for the first time in the literature, it also aims to understand whether HPWS contribute to the development of organizational level capabilities. Furthermore, U-I collaboration is examined as a contextual factor enabling the use of HPWS to transform technological capabilities.